1982
DOI: 10.1128/aem.43.4.877-893.1982
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme immunoassay for detection of Salmonellae in foods

Abstract: An enzyme immunoassay was developed to detect Salmonella in foods. Indirect test protocols were developed for use with microtitration plates or Gilford microcuvettes. Samples from enrichment cultures were mixed with H-specific immunoglobulin G and allowed to react; unbound antibody was removed by three 5-min centrifugation washes; goat anti-rabbit antibody conjugated to alkaline phosphatase was added and allowed to react; and unbound conjugate was removed by centrifugation washing as before. Salmonella-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…typhimurium cells ml-' but the use of a salmonella polyvalent flagella antiserum caused false-positive results. The requirement for assay specificity has led to the purification of flagella antibodies, by removing IgM, and using phosphataselabelled secondary antibody to avoid the interference of bacterial peroxidases (Minnich et al 1982). The authors also found that fixation of cells from food broths to microtitre plates or microcuvettes was inconsistent and so centrifugation was used to remove unbound reagents.…”
Section: Enzyme Lmmunoassaysmentioning
confidence: 99%
“…typhimurium cells ml-' but the use of a salmonella polyvalent flagella antiserum caused false-positive results. The requirement for assay specificity has led to the purification of flagella antibodies, by removing IgM, and using phosphataselabelled secondary antibody to avoid the interference of bacterial peroxidases (Minnich et al 1982). The authors also found that fixation of cells from food broths to microtitre plates or microcuvettes was inconsistent and so centrifugation was used to remove unbound reagents.…”
Section: Enzyme Lmmunoassaysmentioning
confidence: 99%
“…Previous attempts to devise Salmonella-specific immunoassays using mixtures of polyclonal antibodies yielded many false positives because of the presence of cross-reacting components in the antisera [52]. Since antibodies generated against somatic antigens of Salmonella are primarily of the IgM type, use of purified IgG component of polyclonal antisera decreased the cross-reactivity [53] but did not completely eliminate it [54]. Also, batch-to-batch variations in the reactivity and titers of polyclonal antisera create problems in devising a standard test for routine quality control use.…”
Section: Salmonellamentioning
confidence: 99%
“…Many attempts have been made to accelerate, simplify and improve the reliability of detection methods. Among these are the fluorescent antibody test (Rodrigues and Kroll, 1990;Tsai and Slavik, 1994), various enzyme-linked antibody tests (Minnich et al, 1982;Flowers et al, 1988), DNA hybridization methods (Fitts et al, 1983) and improved culturing methods (Poppe and Duncan, 1996). Most such tests have shown considerable degrees of success, but most require about 8-10 hr from initial sampling to final results.…”
Section: Introductionmentioning
confidence: 99%